MALIGNANT CLIVAL CHORDOMA IN A CHILD WITH TURNER SYNDROME DIAGNOSED AFTER 4 YEARS OF GROWTH HORMONE THERAPY - A, Julia; I, Arini Nuran; L, Poi Giok (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Paediatric chordomas are rare malignant tumours originating from primitive notochordal remnants with a high recurrence rate. Only 5% of them occur in the first two decades; less than 300 paediatric cases have been described so far in the literature. Turner syndrome has been found to be associated with an increased rate of extragonadal neoplasm, sporadic report of Turner syndrome with various brain tumours such as medulloblastoma and meningioma have been found in the literature. However to date there’s insufficient data to establish a definite relationship between brain tumours and Turner Syndrome. CASE We described the first case of a 14-year-old girl with underlying Turner Syndrome who was started on growth hormone therapy for the past 4 years. She achieved good height velocity with no side effects reported and her serial IGF-1 was within normal range. She developed intermittent headache which later associated with bilateral distal upper limb weakness and numbness. Presence of upper motor neuron signs on examination prompted further evaluation with MRI of brain and spine which revealed a deep seated cystic lesion occupying the prepontine and retropharyngeal region measuring 5.9 cm x 4.8 cm x 6.8 cm. Histopathological examination of the mass biopsied confirmed the diagnosis of clival chordoma. Parents have opted for conservative management in view of high operative risk. CONCLUSION Current literature reviewed; no case of chordoma and Turner Syndrome that has been reported to date. Although Turner’s syndrome is not one of the congenital chromosomal abnormalities which demand routine CNS screening, neuroimaging should be done in patients with Turner Syndrome that presents with neurological symptoms